The analysis of Serbian customers satisfaction with e-services quality dimensions of lodging e-intermediaries - Mihajlović, Nikola (The European Journal of Applied Economics, 2017)
With the constantly rising share of online accommodation bookings, finding out how customers perceive the website e-service quality is becoming increasingly important in order to build strong satisfaction and create loyal customers. The main goal of the study was to analyze how Serbian customers perceive the quality of service provided by lodging e-Intermediaries. Correlation matrix and multiple regression analysis were used to determine the impact of each of 6 of e-service quality dimensions on satisfaction of e-intermediary customers. As a convenience sampling approach was used, the sample comprised mostly of tourism and hospitality professionals, university staff and students. The questionnaires were distributed via e-mails, social media and partially directly in printed form during the research period of 3 months (July-September, 2015). In total, 148 respondents participated in the research. The study has shown that only three out of six dimensions have impact on customer satisfaction, comprising 63.9% of total customer satisfaction: reliability, information quality, and personalization.